PORTRAIT OF EFL LEARNERS’ WRITINGS: ERRORS, CHALLENGES AND SOLUTIONS - Ira Irzawati; Anastasia Ronauli Hasibuan; Valensia Giovanni (Universitas PGRI Palembang, 2021)
This study aimed to analyze EFL learners’ writings. It focused on portraying the most dominant grammatical and lexical errors in writing. It also explored challenges and alternative solutions from students’ perspectives. A qualitative approach in terms of descriptive design was applied in this study. The participants were thirty sophomores from four different faculties of a private university that were selected using stratified random sampling. Writing test, questionnaire, and interview were instruments to collect the data. Collecting, identifying, classifying, and describing were modified data analysis stages used in this study. The results revealed 445 grammatical errors and 111 lexical errors found in students’ writing. Limited knowledge of grammar and vocabulary, lack of practice and motivation, and unsatisfactory writing skills are the most common students’ writing challenges. The students also believed that review and feedback, various material, exercise and assignment exposure, and supporting technological tools are alternative solutions to anticipate the errors and challenges. The data of writing errors, challenges, and alternative solutions provide beneficial insights for the lecturers to formulate proper teaching methods, materials, and activities in writing.